2005
DOI: 10.1128/jcm.43.12.6209-6211.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of a Panton-Valentine Leucocidin-Positive, Methicillin-Resistant Staphylococcus aureus Strain between Humans and a Dog

Abstract: Panton-Valentine leucocidin-positive methicillin-resistant Staphylococcus aureus (MRSA) strains with identical resistance patterns were cultured from recurrent infections of a 51-year-old patient, her healthy husband, son, and dog, and pulsed-field gel electrophoresis showed that all MRSA strains were indistinguishable. CASE REPORTIn 2002, a 51-year-old female patient with a diabetic foot was admitted to the surgical ward of a Dutch teaching hospital in the province Overijssel. Cultures were taken from the ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 17 publications
1
54
0
1
Order By: Relevance
“…Several studies have implicated hospital surfaces contaminated with nosocomial pathogens, including MRSA, in the dissemination of hospital-acquired infections (Rampling et al 2001, Schultsz et al 2003, Hota 2004, Kramer et al 2006, Sexton et al 2006, Boyce 2007, Weber et al 2010, Otter et al 2011. Paralleling these are reports of the increasing role of MRSA in nosocomial infections in veterinary settings (Seguin et al 1999, Leonard, et al 2006, Weese et al 2007, Benedict et al 2008, McLean and Ness 2008, van Duijkeren et al 2010. A recent study of veterinary teaching hospitals accredited by the American Veterinary Medicine Association (AVMA) found that MRSA was the second most common pathogen (13/31, 42%) associated with nosocomial outbreaks (Benedict et al 2008).…”
Section: Introductionmentioning
confidence: 76%
“…Several studies have implicated hospital surfaces contaminated with nosocomial pathogens, including MRSA, in the dissemination of hospital-acquired infections (Rampling et al 2001, Schultsz et al 2003, Hota 2004, Kramer et al 2006, Sexton et al 2006, Boyce 2007, Weber et al 2010, Otter et al 2011. Paralleling these are reports of the increasing role of MRSA in nosocomial infections in veterinary settings (Seguin et al 1999, Leonard, et al 2006, Weese et al 2007, Benedict et al 2008, McLean and Ness 2008, van Duijkeren et al 2010. A recent study of veterinary teaching hospitals accredited by the American Veterinary Medicine Association (AVMA) found that MRSA was the second most common pathogen (13/31, 42%) associated with nosocomial outbreaks (Benedict et al 2008).…”
Section: Introductionmentioning
confidence: 76%
“…Rifampin was used effectively in conjunction with ciprofloxacin (van Duijkeren et al 2005, Sing et al 2008) and doxycycline (van Duijkeren et al 2004) with subsequent negative nares cultures for the pet animal. The ciprofloxacin/ rifampin combination appeared to be effective in curbing further human infection in case of a colonized cat and dog (van Duijkeren et al 2005, Sing et al 2008, although the cat was not resampled to confirm clearance of MRSA (Sing et al 2008). In one case (Manian 2003), 5% vancomycin ointment was used in the nares of both infected humans and the colonized dog, but complications resulted before all subjects were free of colonization and infection.…”
Section: Bramble Et Almentioning
confidence: 99%
“…Everyone was treated with rifampicin and ciprofloxacin. After six months of treatment, no new samples were recovered in the tests for detection of CA-MRSA among the family members and the dog (Van Duijkeren et al, 2005).…”
Section: Case Reportsmentioning
confidence: 99%
“…Cases of S. aureus with intermediate resistance to vancomycin (VISA) in addition to presenting heteroresistance are increasingly common in health centers where MRSA infections are treated with vancomycin (Trakulsomboon et al, 2001;Van Duijkeren et al, 2005;Kim et al, 2000).…”
Section: Vancomycin Resistancementioning
confidence: 99%
See 1 more Smart Citation